Sanctuaries in Roman Dacia : materiality and religious experience - Szabó, Csaba (Archaeopress Roman archaeology, 2018)
This text focuses on lived ancient religious communication in Roman Dacia. Testing for the first time the 'Lived Ancient Religion' approach in terms of a peripheral province from the Danubian area, this work looks at the role of 'sacralised' spaces, known commonly as sanctuaries in the religious communication of the province.